Y-box protein-1/p18 as novel serum marker for ovarian cancer diagnosis: A study by the Tumor Bank Ovarian Cancer (TOC). (September 2016) - Rohr, Irena; Braicu, Elena I.; En-Nia, Abdelaziz; Heinrich, Michaela; Richter, Rolf; Chekerov, Radoslav; Dechend, Ralf; Heidecke, Harald; Dragun, Duska; Schäfer, Reinhold; Gorny, Xenia; Lindquist, Jonathan A.; et al.
Highlights: Significantly lower serum levels of YB-1/p18 in EOC patients than in healthy controls. YB-1/p18 can be quantified easily by using sandwich ELISA assays. YB-1/p18 could be useful for early detection of EOC. Abstract: Introduction: The cold shock Y-box binding protein-1 (YB-1) fulfills important roles in regulating cell proliferation and differentiation. Overexpression occurs in various tumor cells. Given the existence of extracellular YB-1 we set out to determine the diagnostic, predictive and prognostic role of serum YB-1/p18 for patients with primary epithelial ovarian cancer (EOC). Methods: The protein fragment YB-1/p18 was quantified by sandwich ELISA in serum samples from 132 healthy female volunteers and 206 patients with histological diagnosis of primary EOC. The ELISA sensitivity and specificity to detect EOC were calculated using receiver operating curves. Survival data were calculated using Kaplan Maier curves. Results: Median age at the time of diagnosis was 60 years and follow-up ended with a mean of 44.8 month. 188 (91%) patients were diagnosed at advanced stages (FIGO III/IV) and 188 patients (91%) suffered from high-grade serous ovarian carcinoma. YB-1/p18 levels were significantly decreased in older patients (p = 0.021). Significantly lower serum levels of YB-1/p18 were detected in the EOC cohort when compared to the control group (p < 0.0001, AUC = 0.827; 95% CI, 0.787–0.867). Using the expression of serum YB-1/p18 in early stages I and II cases these could be differentiated from control cases (p < 0.0001, AUC = 0.816; 95% CI 0.704–0.929). No other significant associations between clinical prognostic factors and YB-1/p18 serum levels were detected. Immunoblotting results with serum samples suggest that masking of epitopes by the YB-1/p18 fragment in multiprotein-complexes under non reducing conditions leads to the observed reduced ELISA readings in the EOC cohort. Conclusions: The quantification of fragment YB-1/p18 derived from cold shock protein YB-1 in serum samples could be useful for the early diagnosis of EOC.